The role of the CXCL12/CXCR4 axis in monocyte tissue compartmentalisation and homeostasis - Evrard, Maximilien (2017)
Monocytes are integral to innate immune responses against microbial and sterile tissue injury. However, mechanisms that regulate their compartmentalisation in distinct tissues and their rapid mobilisation following inflammatory signals remain poorly understood. Using bone marrow (BM) intravital imaging and BrdU pulsing assays, we found that while all monocytes respond to mobilisation cues, only a minority is able to enter the peripheral circulation, suggesting a heterogeneity among monocytes. Using computational analysis approaches to interpret multi- dimensional datasets, we demonstrate that BM Ly6Chi monocytes consist of two distinct subpopulations (CXCR4hi and CXCR4lo subpopulations) in both mice and humans. Transcriptome studies and in vivo assays revealed functional differences between the two subpopulations. Notably, the CXCR4hi subset proliferates and is immobilized in the BM for the replenishment of functionally mature and mobilisable CXCR4lo monocytes. We propose that the CXCR4hi subset represents a "transitional pre-monocyte" population and this sequential step of maturation serves to maintain a stable pool of BM monocytes. Additionally, reduced CXCR4 expression on monocytes, upon their exit into the circulation, does not reflect its diminished role in monocyte biology. Specifically, CXCR4 regulates monocyte peripheral cellular activities by governing their circadian oscillations, homing to BM and splenic reservoirs and pulmonary margination. Importantly, we showed that reduced monocyte margination through CXCR4 inhibition resulted in decreased occurrence of lung injury and mortality in mouse models of sepsis. Altogether, our study demonstrates the multifaceted role of CXCR4 in defining BM monocyte heterogeneity and in regulating their function in peripheral tissues.